31 Survival outcomes in endometrial cancer patients having lymphadenectomy, sentinel node mapping followed by lymphadectomy and sentinel node mapping alone: long-term results of a propensity-matched analysis. (13th November 2020) - Bogani, G; Pinelli, C; Ditto, A; Casarin, J; Ghezzi, F; Raspagliesi, F
Abstract : Objective: Sentinel node mapping (SLNM) has replaced lymphadenectomy for staging surgery in apparent early-stage endometrial cancer (EC). Here, we evaluate long-term survival of three different approaches of nodal assessment in EC. Methods: This is a multi-institutional retrospective study evaluating long-term outcomes (at least 3 years) of patients having lymphadenectomy, SLNM followed by lymphadenectomy and SLNM alone. We applied a propensity-matched algorithm. Survival outcomes were assessed using Kaplan-Meier and Cox proportional hazard models Results: Applying a propensity score matching algorithm we selected 180 patients having SLNM (90 SLNM vs. 90 SLNM followed by lymphadenectomy). Additionally, a control group of 180 patients having lymphadenectomy was selected. Overall, 10% of patients were diagnosed with positive nodes. Low volume disease was observed in 16 cases (5 micrometastasis and 11 isolated tumor cells). Patients having SLNM followed by lymphadenectomy had a higher possibility to be diagnosed with a stage IIIC disease in comparison to lymphadenectomy alone (p=0.02); while we did not observe a difference in the diagnostic value of SLNM followed by lymphadenectomy and SLNM (p=0.389). Median follow-up time was 69 (7–206) months. There were no statistical differences in terms of disease-free (p=0.570, log-rank test) and overall survival (p=0.911, log-rank test); Similarly, they did not impact on survival outcomes after stratification by low, intermediate and high-risk patients. Conclusions: Our study highlighted that SLNM provides similar long-term oncologic outcomes than lymphadenectomy, even in high-risk patients. Further evidence is warranted to assess the prognostic value of low volume disease detected by ultrastaging in patients following SLNM.